2023
DOI: 10.1038/s41375-022-01780-1
|View full text |Cite
|
Sign up to set email alerts
|

Romidepsin-CHOEP followed by high-dose chemotherapy and stem-cell transplantation in untreated Peripheral T-Cell Lymphoma: results of the PTCL13 phase Ib/II study

Abstract: The standard treatment for young patients with untreated PTCLs is based on anthracycline containing-regimens followed by high-dose-chemotherapy and stem-cell-transplantation (HDT + SCT), but only 40% of them can be cured. Romidepsin, a histone-deacetylase inhibitor, showed promising activity in relapsed PTCLs; in first line, Romidepsin was added with CHOP. We designed a study combining romidepsin and CHOEP as induction before HDT + auto-SCT in untreated PTCLs (PTCL-NOS, AITL/THF, ALK-ALCL), aged 18–65 years. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Overall, baseline [cfDNA] was assessable in 75 patients, whose characteristics and outcome are listed in Tables S1-S5 and overlap with those of the population enrolled in the PTCL13 study. 10 Cell-free DNA concentration, expressed in ng of cfDNA/ mL of plasma (ng/mL), had a median value of 19.1 ng/mL (range: 2.27-1082) and it was associated with clinical risk factors (Figure 1A-E). There was a strong association between high [cfDNA] and a high IPI (median cfDNA: IPI 0-2 = 12.27, IPI 3-5 = 63.86 ng/mL, p < 0.0001) and PIT scores (median cfDNA: PIT 0-1 = 14.20, PIT 2-4 = 31.22 ng/mL, p = 0.0006), increased LDH levels (median cfDNA: normal LDH = 10.1, increased LDH = 40 ng/mL p < 0.0001) and poor performance status (median cfDNA: Eastern Cooperative Oncology Group performance status of 0 = 12.27, performance status ≥1 = 37 ng/mL, p = 0.0003).…”
Section: R E Su Lts a N D Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, baseline [cfDNA] was assessable in 75 patients, whose characteristics and outcome are listed in Tables S1-S5 and overlap with those of the population enrolled in the PTCL13 study. 10 Cell-free DNA concentration, expressed in ng of cfDNA/ mL of plasma (ng/mL), had a median value of 19.1 ng/mL (range: 2.27-1082) and it was associated with clinical risk factors (Figure 1A-E). There was a strong association between high [cfDNA] and a high IPI (median cfDNA: IPI 0-2 = 12.27, IPI 3-5 = 63.86 ng/mL, p < 0.0001) and PIT scores (median cfDNA: PIT 0-1 = 14.20, PIT 2-4 = 31.22 ng/mL, p = 0.0006), increased LDH levels (median cfDNA: normal LDH = 10.1, increased LDH = 40 ng/mL p < 0.0001) and poor performance status (median cfDNA: Eastern Cooperative Oncology Group performance status of 0 = 12.27, performance status ≥1 = 37 ng/mL, p = 0.0003).…”
Section: R E Su Lts a N D Discussionmentioning
confidence: 99%
“…Thus, the aim of this study was to assess whether pretreatment [cfDNA] in plasma was associated with clinical risk factors and prognosis in patients enrolled in the PTCL13 clinical trial (NCT02223208), whose plasma samples were prospectively collected. This was a multicentre phase Ib‐II study that included newly diagnosed patients affected by peripheral T‐cell lymphoma, not otherwise specified (PTCL‐NOS), anaplastic lymphoma kinase‐negative anaplastic large‐cell lymphoma (ALK‐ALCL) and nodular T‐follicular helper lymphoma (nTFHL), whose results have been recently published 10 . Patients received 6 cycles of chemotherapy combined with romidepsin, followed by consolidation with haematopoietic stem cell transplantation, in those who achieved a response to induction and were eligible to the procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Similarly, a phase III trial comparing romidepsin plus CHOP versus CHOP failed to meet its primary endpoint of PFS, 13 and a related phase II trial of romidepsin plus CHOEP and HDT/ASCR failed to meet a prespecified PFS. 14 These trials demonstrate that the addition of an active agent to chemotherapy may not result in increased survival, although a critical distinction in the above examples is that alemtuzumab and romidepsin significantly increased toxicity compared with standard chemotherapy (which was not observed with BV-CHP). In our trial, lenalidomide added excess hematologic toxicity which prevented patients from actually completing induction.…”
Section: Discussionmentioning
confidence: 99%
“…However, two randomized phase III trials of alemtuzumab plus CHOP versus CHOP showed no increase in survival owing to increased toxicity 11,12 . Similarly, a phase III trial comparing romidepsin plus CHOP versus CHOP failed to meet its primary endpoint of PFS, 13 and a related phase II trial of romidepsin plus CHOEP and HDT/ASCR failed to meet a prespecified PFS 14 . These trials demonstrate that the addition of an active agent to chemotherapy may not result in increased survival, although a critical distinction in the above examples is that alemtuzumab and romidepsin significantly increased toxicity compared with standard chemotherapy (which was not observed with BV‐CHP).…”
Section: Discussionmentioning
confidence: 99%